Short and long versions of a 12-week netball specific neuromuscular warm-up improves landing technique in youth netballers. (May 2021) - Belcher, Suzanne; Whatman, Chris; Brughelli, Matt; Borotkanics, Robert
Abstract: Objective: To investigate the efficacy of two 'NetballSmart', netball specific warm-ups in improving landing technique measures in New Zealand secondary school netball players. Design: Multi-site cluster experimental trial. Participants: 77 youth participants, mean ± SD age = 15.8 ± 0.9 were recruited from secondary school netball teams. Setting: 12 teams from 6 schools performed either the NetballSmart Dynamic Warm-up (NSDW) (n = 37); or Power warm-up (PWU) (n = 40), three times a week for 12 weeks. All players within a school (2 teams) were assigned the same warm-up, avoiding treatment contamination. Main outcome measures: A series of unilateral and bilateral drop vertical jumps on to a portable force plate were completed by all participants. Measures included peak vertical ground reaction force (GRF) for single-leg and bilateral landings; frontal plane projection angle (FPPA) for right and left single-leg landings and Landing error scoring system (LESS) for bilateral landings. Paired t-tests were used to assess mean differences pre and post the warm-up. Generalised linear mixed effects models were developed to evaluate the effects between the NSDW and PWU groups. Results: Significant improvements were found in all the landing technique outcome measures for both warm-up groups (ES Range- GRF  = −0.6 to −1.1; FPPA  = 0.8 to 1.2; LESS  = −1.6 to-3.2; p < 0.05). Results of mixed effects models revealed that there was only a significantly greater improvement in LESS for the PWU group (β = −0.30, p = 0.001). Conclusion: Results show both warm-ups can improve landing technique measures in youth secondary school netball players. It is recommended that coaches should consider implementing one of the two warm-ups in their netball programmes. Their choice of warm-up will likely be dependent on their environment and time demands. Highlights: The NetballSmart dynamic warm-up and NetballSmart Power warm-up both significantly improved landing technique over a 12-week training period in youth female netball players. The longer (NSDW) warm-up was not superior to the shorter (PWU) and we recommend that coaches should consider implementing either in their netball programmes, choice of which will likely be dependent on the environment. We recommend coaches have access to a teaching programme on how to use the warm-up programmes, safely and effectively. Teaching programmes for coaches should focus on analysing and correcting movement technique in the warm-up, whilst developing the ability to adapt the programme to improve motivation yet retain exercise effectiveness.